Fracture resistance of endodontically treated premolars with direct composite restorations - Moezizadeh, Maryam (Medknow Publications, 2011)
PURPOSE: To determine the fatigue resistance and failure mode of endodontically treated premolars using direct composite resin restorations. MATERIALS AND METHODS: Eighty-four human premolars were divided into seven groups of 12, prepared as follows: Intact teeth used in Group 1 as control, the second group covers the endodontically treated teeth, restored with direct onlays using Z250 composite resin, the next two groups (i.e. 3,4) were similar to the second group, but subjected to 1 and 2 million fatigue load cycles, respectively. Groups 5, 6, 7 were similar to groups 2, 3, 4, however, in these groups Tetric Ceram was used as the restorative material. All specimens were loaded using a Universal Testing Machine until fracture occurred. One-way Anova andTukey's HSD tests were used to analyze the data of onlay groups. RESULTS: All specimens withstood the masticating simulation. The mean fracture strength for Goups 1 to 7 was: 1276.92, 1373.47, 1269/70, 486/35, 484/12, 1130/49, 1113/79 Newton, respectively. No statistically significant differences were found between the groups in fracture strength and failure mode. CONCLUSIONS: No statistically significant differences in fracture strength were found between sound teeth and composite onlays that were subjected to 1 and 2 million fatigue load cycles.